Milk Production and resource use efficiency of dairy farming under stall-fed condition in Karnataka - Deshetti, Mallu Basanagouda; Teggi, Mahantesh Y; Hosamani, S V (Indian Journal of Dairy Science, 2017)
In Karnataka, Vijayapura and Bagalakote districts have large numbers of the buffalo and wherein dairy enterprise is fast growing. The study attempted to estimate the economics of stall feeding and resource use efficiency in buffalo rearing. Primary data pertaining to the 2013-14 agricultural year collected from 52 sample respondents in Vijayapura and Bagalakote districts. The findings revealed that the initial investment in dairy enterprise in respect of buffalo (52in number) accounted ₹1,23,910 per herd. The average maintenance cost incurred per herd per annum including amortized cost of initial investment was ₹1,32,443 in buffalo-based diary enterprise, the herd size of buffalo being 2.77. The net return was found to be ₹41,379 per herd per year and the benefit-cost ratio was 1.31 in buffalo rearing. In Vijayapura, the marginal value product (MVP) to Marginal fixed cost (MFC) ratio was negative for medical expenditure (-0.111) in buffalo farms, while it was negative for miscellaneous expenditure (-0.23) in Bagalakote.